Characterization of glycoconjugates in the pharyngeal cavity and the oesophagus of Odontesthes bonariensis by lectins - Alcira Ofelia Díaz; María Florencia Tano de la Hoz; Alicia Mabel García; Alicia Haydée Escalante; Adriana Lía Goldemberg (Biotemas, 2012)
Seven types of biotinylated lectins were used to examine glycoconjugates (GCs) expression patterns in the mucosa of the pharyngeal cavity and the oesophagus of Odontesthes bonariensis. Con-A, RCA-I, and WGA binding sites were positive for glycocalyx, epithelial cells, and mucous cells in both organs with similar reaction patterns. PNA just stained glycocalyx and epithelial cells in the mucosa in both organs. DBA, SBA, and UEA-I stained only the oesophagus, and a greater affinity to glycocalyx and the epithelial cells was observed. The results of this study were discussed and their possible functional implications were compared.